Increased rectal microbial richness is associated with the presence of colorectal adenomas in humans - Sanapareddy, Nina; Legge, Ryan M; Jovov, Biljana; McCoy, Amber; Burcal, Lauren; Araujo-Perez, Felix; Randall, Thomas A; Galanko, Joseph; Benson, Andrew; Sandler, Robert S; Rawls, John F; Abdo, Zaid; et al. (The ISME Journal, 2012)
Differences in the composition of the gut microbial community have been associated with diseases such as obesity, Crohn’s disease, ulcerative colitis and colorectal cancer (CRC). We used 454 titanium pyrosequencing of the V1–V2 region of the 16S rRNA gene to characterize adherent bacterial communities in mucosal biopsy samples from 33 subjects with adenomas and 38 subjects without adenomas (controls). Biopsy samples from subjects with adenomas had greater numbers of bacteria from 87 taxa than controls; only 5 taxa were more abundant in control samples. The magnitude of the differences in the distal gut microbiota between patients with adenomas and controls was more pronounced than that of any other clinical parameters including obesity, diet or family history of CRC. This suggests that sequence analysis of the microbiota could be used to identify patients at risk for developing adenomas.